CD81 and CD82 expressing tumor-infiltrating lymphocytes in the NSCLC tumor microenvironment play a crucial role in T-cell activation and cytokine production - Na, Kwangmin; Lee, Seul; Kim, Dong Kwon; Kim, Young Seob; Hwang, Joon Yeon; Kang, Seong-san; Baek, Sujeong; Lee, Chai Young; Yang, Seung Min; Han, Yu Jin; Kim, Mi hyun; Han, Heekyung; et al. (Frontiers in Immunology, 2024)
To understand the immune system within the tumor microenvironment (TME) of non-small cell lung cancer (NSCLC), it is crucial to elucidate the characteristics of molecules associated with T cell activation. We conducted an in-depth analysis using single-cell RNA sequencing data obtained from tissue samples of 19 NSCLC patients. T cells were classified based on the Tumor Proportion Score (TPS) within the tumor region, and molecular markers associated with activation and exhaustion were analyzed in T cells from high TPS areas. Notably, tetraspanins CD81 and CD82, belonging to the tetraspanin protein family, were found to be expressed in activated T cells, particularly in cytotoxic T cells. These tetraspanins showed strong correlations with activation and exhaustion markers. In vitro experiments confirmed increased expression of CD81 and CD82 in IL-2-stimulated T cells. T cells were categorized into CD81 high CD82 high and CD81 low CD82 low groups based on their expression levels, with CD81 high CD82 high T cells exhibiting elevated activation markers such as CD25 and CD69 compared to CD81 low CD82 low T cells. This trend was consistent across CD3 + , CD8 + , and CD4 + T cell subsets. Moreover, CD81 high CD82 high T cells, when stimulated with anti-CD3, demonstrated enhanced secretion of cytokines such as IFN-γ, TNF-α, and IL-2, along with an increase in the proportion of memory T cells. Bulk RNA sequencing results after sorting CD81 high CD82 high and CD81 low CD82 low T cells consistently supported the roles of CD81 and CD82. Experiments with overexpressed CD81 and CD82 showed increased cytotoxicity against target cells. These findings highlight the multifaceted roles of CD81 and CD82 in T cell activation, cytokine production, memory subset accumulation, and target cell cytolysis. Therefore, these findings suggest the potential of CD81 and CD82 as promising candidates for co-stimulatory molecules in immune therapeutic strategies for cancer treatment within the intricate TME.